The Impact of an Application of Telerehabilitation Technology on Caregiver Burden - Tindall, Lyn R. (Int J Telerehabil, 2009)
The objective of this research was to assess the effects of an application of telerehabilitation reducing time and financial obligation on caregiver burden among eleven caregivers of elderly persons with Parkinson’s disease. Clients (care receivers) participated in speech therapy delivered via videophones in their homes; the protocol required 16 treatments delivered four times a week for four weeks. At the conclusion of treatment, caregivers completed a structured interview about the impact of telerehabilitation on time and financial aspects of the burden of care. On average, this speech therapy protocol delivered by videophones saved 48 hours of time, more than 92 hours of work time, and $1024 for each caregiver. Savings were significant and previous research demonstrated nearly equal outcomes using the videophone delivery method. Implications for practice and research are discussed.